Efeitos do turismo de pesca esportiva na Comunidade de Terra Preta - Roraima - Negrão, Daniel de Souza (2018)
The act of traveling is an ancient practice in the world, and the Amazon region has attracted many travelers who seek rest from their daily lives and who find in sports tourism a leisure option, but something that can not be overlooked are the environmental effects, economic and social that tourism generates in the place of execution of such activity. This work aims to describe the effects of sports fishing tourism in the community of Terra Preta, Caracaraí - RR, where a description of the community was carried out, together with the identification of the work undertakenprior to the tourism in the place associated with the quantification and analysis of the effects of tourism on the family unit and in the community. And to answer the proposed objectives were accomplished semi-structured interviews with 24 families of the Terra Preta community, Caracaraí - RR, and community observation in three divided times in the years 2017 and 2018. The information found in visiting community reveals positive effects with greater prominence is the generation of jobs, generating visible economic growth in the locality, but in return the tourism brought with it disputes over this capital, changes in the habits of the people. With the information collected and analyzed, it was concluded that the tourism activity of sport fishing brought benefits to the community of Terra Preta, Caracaraí - RR, effects that are observed with the improvement of the houses, with the concern of the local residents with the environment and the retraction of deforestation, but in return for money stemmed disputes that shakes you and m PIRIT family and community residents.